The preventive effect of vitamin C on the cellular and functional integrity of kidney cells in rats following repeated exposure to paraquat - Benjamin Nnamdi Okolonkwo; Edna Ogechi Nwachuku; Pascal Chuka Ene; Chukwubuike Udoka Okeke (MDPI AG, 2014)
Paraquat (PQ) is a bipyridylium herbicide that is applied around trees in orchards and between crop rows to control broad-leaved and grassy weeds. Its oxidation results in the formation of superoxides which causes damage to cellular components. In this study, we determined the antioxidant effect vitamin C has on the cellular integrity of kidney function in rats following repeated exposure to PQ. Ninety-six male rats, grouped twelve rats per subgroup (A, Avit.c, B, Bvit.c, C, Cvit.c, D and Dvit.c) were intraperitoneally injected with different sublethal increasing doses (0, 0, 2, 2, 4, 4, 6 and 6 mg/kg body weight) of PQ respectively on biweekly (14 days) intervals over a period of three months (84 days). Subsequently, the subgrouped animals (Avit.c, Bvit.c, Cvit.c and Dvit.c) were maintained orally with 1 g/L vitamin C, while the other subgrouped animals (A, B, C and D) received drinking water with negligible vitamin content throughout the study period. At the end of each monthly (28 days) treatment, four animals per subgroup were selected. Urine samples were collected from each of the selected rats, after which each of the animals were anaesthetized with gaseous isoflurane and 5 mL of blood samples were collected using cardiac puncture procedure. The animals were later decapitated and their kidneys harvested. The samples collected were analyzed for urine [specific gravity (SG), pH, protein and glucose], blood (urea, creatinine, total protein and glucose), and the histological studies on kidney slides. The dose and exposure- time dependent PQ toxicity resulted in the reduction in urinary pH, elevation in urinary SG, and the detectable presence of protein and glucose in urine. It also caused marked elevation in serum urea and creatinine levels with reduction in serum protein and glucose levels and alterations in the cellular integrity of the renal architecture, especially the glomeruli and tubular tissues. Treatments on the PQ insulted animals with vitamin C resulted in the significant presentation of biochemical and histological values that were a complete reversal or near normalization in the parameters assayed, except the urinary pH which presented with more acidic values (vitamin C is acidic in solution). Vitamin C treatment significantly brought down the urine SG level to normal or near normal. It caused near or total disappearance of protein and glucose in urine, reduction in serum urea and creatinine concentration and elevation or normalization of serum total protein and glucose values with restoration of the renal function of treated rats. These findings clearly show that vitamin C has an important role to play in the body's antioxidant defense system. Its use caused normalization of the biochemical and histological parameters studied and restored the health status of the affected animals.